The Role of Social Media for Disasters in The Era of Disruption (Analysis of Responsiveness to COVID-19 Pandemics on Twitter) - Rahmanto, Fajar; Rafi, Muhammad (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
Social media has become the choice as a means to access various information related to disasters. This article aims to determine the level of public responsiveness to the COVID-19 pandemic disaster through social media Twitter. The research method uses descriptive qualitative with a literature study approach. Sources of information were collected from Twitter using N-Capture regarding the COVID-19 pandemic in March 2020. For data analysis techniques using the NVivo12 Plus software with a query analysis approach. The results showed the community's responsiveness to the COVID-19 pandemic disaster since the advent of the COVID-19 outbreak in Indonesia in early March was enlivened with hashtags (# lawancovid19) of 14,930 counts. Through hashtag # lawancovid19, the bnpb-Indonesia account with (35.24%) and the ministry of health ministry account (20.68%) are the two twitter accounts used most the taggar. The #lawancovid19 narrative on Twitter developed by the Government is a form of information and education communication (IEC) actions regarding the COVID-19 pandemic as part of a preventive effort to prevent the spread of an increasingly widespread pandemic outbreak. Thus, social media can be utilized by the Government and the community to increase effectiveness and efficiency in disseminating disaster information.